2020
DOI: 10.3390/molecules26010027
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Properties of Nature-Inspired N,N′-Alkylated Riboflavin Semiconductors

Abstract: A series of novel soluble nature-inspired flavin derivatives substituted with short butyl and bulky ethyl-adamantyl alkyl groups was prepared via simple and straightforward synthetic approach with moderate to good yields. The comprehensive characterization of the materials, to assess their application potential, has demonstrated that the modification of the conjugated flavin core enables delicate tuning of the absorption and emission properties, optical bandgap, frontier molecular orbital energies, melting poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…According to the SEM images, the riboflavin appeared to precipitate during the electrochemical treatment in a micro‐needle type structure. Such structures are reported in the literature for similar molecules like synthetic flavins, [ 15,27 ] anthraquinones, [ 48,49 ] or other organic pigments. [ 50,51 ] This deposited layer might be an explanation for the comparably low H 2 O 2 production with riboflavin at pH = 2.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…According to the SEM images, the riboflavin appeared to precipitate during the electrochemical treatment in a micro‐needle type structure. Such structures are reported in the literature for similar molecules like synthetic flavins, [ 15,27 ] anthraquinones, [ 48,49 ] or other organic pigments. [ 50,51 ] This deposited layer might be an explanation for the comparably low H 2 O 2 production with riboflavin at pH = 2.…”
Section: Resultsmentioning
confidence: 72%
“…[ 23,24 ] great scientific effort is made for synthesizing variations of flavin analogs with tailored properties for applications as organic semiconductors. [ 25–27 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, an effect of prolongation of the conjugated system on the optical, electrochemical and thermal properties of selected flavins was studied (see Scheme 7) [85] . It was also shown that N ‐alkylation can prevent hydrogen bonding, increase solubility and strongly enhance fluorescence while maintaining high thermal stability [87] . The flavin photocatalysis involves the triplet state as the active species in most cases and it can be, in principle, used for reductions as well as for oxidation reactions [88] .…”
Section: High‐performance Organic Pigments and Organic Dyes In Solar‐...mentioning
confidence: 99%
“…[85] It was also shown that N-alkylation can prevent hydrogen bonding, increase solubility and strongly enhance fluorescence while maintaining high thermal stability. [87] The flavin photocatalysis involves the triplet state as the active species in most cases and it can be, in principle, used for reductions as well as for oxidation reactions. [88] Consequently, flavins have been employed in numerous organic photoredox-catalyzed reactions.…”
Section: Flavin-based Materialsmentioning
confidence: 99%